If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying ln(x + 5) = 2ln(x + -1) Reorder the terms: ln(5 + x) = 2ln(x + -1) (5 * ln + x * ln) = 2ln(x + -1) (5ln + lnx) = 2ln(x + -1) Reorder the terms: 5ln + lnx = 2ln(-1 + x) 5ln + lnx = (-1 * 2ln + x * 2ln) 5ln + lnx = (-2ln + 2lnx) Solving 5ln + lnx = -2ln + 2lnx Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Add '2ln' to each side of the equation. 5ln + 2ln + lnx = -2ln + 2ln + 2lnx Combine like terms: 5ln + 2ln = 7ln 7ln + lnx = -2ln + 2ln + 2lnx Combine like terms: -2ln + 2ln = 0 7ln + lnx = 0 + 2lnx 7ln + lnx = 2lnx Add '-2lnx' to each side of the equation. 7ln + lnx + -2lnx = 2lnx + -2lnx Combine like terms: lnx + -2lnx = -1lnx 7ln + -1lnx = 2lnx + -2lnx Combine like terms: 2lnx + -2lnx = 0 7ln + -1lnx = 0 Factor out the Greatest Common Factor (GCF), 'ln'. ln(7 + -1x) = 0Subproblem 1
Set the factor 'ln' equal to zero and attempt to solve: Simplifying ln = 0 Solving ln = 0 Move all terms containing l to the left, all other terms to the right. Simplifying ln = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(7 + -1x)' equal to zero and attempt to solve: Simplifying 7 + -1x = 0 Solving 7 + -1x = 0 Move all terms containing l to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -1x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -1x = 0 + -7 -1x = 0 + -7 Combine like terms: 0 + -7 = -7 -1x = -7 Add 'x' to each side of the equation. -1x + x = -7 + x Combine like terms: -1x + x = 0 0 = -7 + x Simplifying 0 = -7 + x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| -4.4(3+x)+2=4(x+3.4) | | 6(x-9)+4x=31 | | -104=8a | | 5x+100(90-x)=4440 | | 21+35=7x-7 | | 2(3.4-x)=16.4(x+1.7) | | (2X-4)*5=(4X+1)*8 | | (y+4)*(y-8)= | | 9t^2-3t-6=0 | | 30-3x=0 | | n=1/4+3/8 | | 1089x=9y | | x^2+y^2+10x+6y+9=0 | | y-19.2=6.9 | | 34-3(2w+1)=8w-3(8+w) | | 8-6x=5x+25 | | x^2+24x+144=169 | | a^2-8a=20 | | 6x-11+3x=5+9x-15 | | x^2-y^2=44 | | 4p^2+12p=0 | | (x+y)(x-y)=44 | | 20-(x+8)=6x-2 | | 4y-7-2y+6=0 | | 10x+28=6x+12 | | 10x-7=40x+17 | | 11(3+y)=5(2y+8) | | 3x^2+12x+48=0 | | x^2=2(4-x) | | 24=4(x+4) | | 9x-4y=-37 | | x^2+4(x-3)=0 |